THE IMPLEMENTATION OF THE CYBERNETICS APPROACH IN ISLAMIC ELEMENTARY SCHOOL LEARNING: A STUDY ON TEACHER-STUDENT FEEDBACK SYSTEMS - Diarko, Berxy; Zuhri, Saifuddin; Hasanah , Uswatun; Fardati, Fadhliya; Yusuf, Arief Rahman (Media Inovasi Pendidikan dan Publikasi, 2025)
The implementation of the cybernetics approach in learning has gained attention due to its potential to enhance educational outcomes through dynamic feedback systems. This study aims to explore the application of the cybernetics approach in Islamic elementary school learning, focusing on the teacher-student feedback system as a mechanism to optimize learning processes and outcomes. The research adopts a descriptive qualitative methodology, employing data triangulation through observations, interviews, and document analysis to ensure comprehensive and valid findings. The study reveals three key findings: (1) the feedback system in a cybernetics approach facilitates continuous interaction and adjustment between teachers and students, improving mutual understanding and instructional alignment; (2) effective implementation requires teachers to possess adaptive skills and the ability to interpret feedback constructively; and (3) the feedback system encourages student engagement and accountability in the learning process. These findings highlight the significance of fostering a dynamic and responsive learning environment, particularly in the context of Islamic elementary schools, where moral and ethical values are integral to education. The implications of this study suggest that adopting a cybernetics approach can transform traditional teaching methods, promoting an interactive, student-centered learning environment. This approach supports the development of critical thinking and collaborative skills, which are essential in 21st-century education. The study emphasizes the need for teacher training and institutional support to integrate such innovative methodologies effectively.